2018
DOI: 10.32598/ijt.12.3.477.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of a New Lepidopteran Insecticide, Flubendiamide, in Non-Target Drosophila melanogaster Meigen (Diptera: Drosophilidae)

Abstract: Background: Flubendiamide, comparatively a new pesticide designed to eradicate lepidopteran insect pests is known to have low risk to birds, mammals, fish, algae, honey bees, non-target arthropods, earthworms, soil macro- and micro-organisms, non-target plants as well as sewage treatment organisms; however, the risk assessment for aquatic invertebrates from metabolite could not be finalized with available data. Methods: Different concentrations of flubendiamide (TATA TAKUMI®, Rallis, India) were introduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In addition, levels of soluble TNF‐R1 were correlated with the severity of the disease 29 . Like microbial infections, other xenobiotics could also be detrimental to the health 30,31 . Phytochemicals could help mitigate such adverse effects 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, levels of soluble TNF‐R1 were correlated with the severity of the disease 29 . Like microbial infections, other xenobiotics could also be detrimental to the health 30,31 . Phytochemicals could help mitigate such adverse effects 32 .…”
Section: Discussionmentioning
confidence: 99%
“…John et al 76 demonstrated that vitamin E has the potential to ameliorate dimethoate and malathion-induced OS in rat erythrocytes. Therefore, like other chemicals, OPs contribute to OS and subsequent pathologies that can be ameliorated to some extent by vitamin E [77][78][79][80][81][82][83][84][85][86][87] (Table 1). Eroğlu et al 62 human erythrocytes treated with 1, 10, and 100 μM concentrations of diclorvos.…”
Section: Protective Potential Of Vitamin E Against Op Induced Toxicit...mentioning
confidence: 99%
“…MDCA is derived from Centella asiatica and is known to exert multiple pharmaceutical activities. Exposure to exogenous agents like xenobiotics and pathogens can elicit oxidative stress and subsequent health hazards. MDCA has been reported to restore redox homeostasis, prevent oxidative stress, and maintain mitochondrial membrane potential. , Moreover, it upregulates anti-apoptotic proteins like Bcl-xL and Bcl-2 to impede cell death . MDCA has been demonstrated to impose anti-colitic effects.…”
Section: Introductionmentioning
confidence: 99%